Acute morphine affects the rat circadian clock via rhythms of phosphorylated ERK1/2 and GSK3β kinases and Per1 expression in the rat suprachiasmatic nucleus - Pačesová, Dominika; Volfová, Barbora; Červená, Kateřina; Hejnová, Lucie; Novotný, Jiří; Bendová, Zdeňka (British journal of pharmacology, 2015)
BACKGROUND AND PURPOSE: Opioids affect the circadian clock and may change the timing of many physiological processes. This study was undertaken to investigate the daily changes in sensitivity of the circadian pacemaker to an analgesic dose of morphine, and to uncover a possible interplay between circadian and opioid signalling. EXPERIMENTAL APPROACH: A time-dependent effect of morphine (1 mg·kg(-1) , i.p.) applied either during the day or during the early night was followed, and the levels of phosphorylated ERK1/2, GSK3β, c-Fos and Per genes were assessed by immunohistochemistry and in situ hybridization. The effect of morphine pretreatment on light-induced pERK and c-Fos was examined, and day/night difference in activity of opioid receptors was evaluated by [(35) S]-GTPγS binding assay. KEY RESULTS: Morphine stimulated a rise in pERK1/2 and pGSK3β levels in the suprachiasmatic nucleus (SCN) when applied during the day but significantly reduced both kinases when applied during the night. Morphine at night transiently induced Period1 but not Period2 in the SCN and did not attenuate the light-induced level of pERK1/2 and c-Fos in the SCN. The activity of all three principal opioid receptors was high during the day but decreased significantly at night, except for the δ receptor. Finally, we demonstrated daily profiles of pERK1/2 and pGSK3β levels in the rat ventrolateral and dorsomedial SCN. CONCLUSIONS AND IMPLICATIONS: Our data suggest that the phase-shifting effect of opioids may be mediated via post-translational modification of clock proteins by means of activated ERK1/2 and GSK3β.
Keywords: cirkadiánní proteiny Period; Animals; Morphine; Rats, Wistar; Circadian Clocks; Mitogen-Activated Protein Kinases; cirkadiánní hodiny; mitogenem aktivovaná proteinkinasa 3; Circadian Rhythm; mitogenem aktivovaná proteinkinasa 1; cirkadiánní rytmus; Male; fosforylace; Period Circadian Proteins; mitogenem aktivované proteinkinasy; Mitogen-Activated Protein Kinase 3; krysa rodu Rattus; Suprachiasmatic Nucleus; morfin; kinasa 3 glykogensynthasy; mužské pohlaví; zvířata; Glycogen Synthase Kinase 3; Mitogen-Activated Protein Kinase 1; nucleus suprachiasmaticus; Rats; Phosphorylation; potkani Wistar